2018
DOI: 10.1093/conphys/coy032
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural guidance of Chinook salmon smolts: the variable effects of LED spectral wavelength and strobing frequency

Abstract: We tested Chinook smolt response to combinations of spectra and strobing frequencies emitted from an underwater LED light, designed to guide fish near water diversion infrastructure. Whilst strobing did not alter fish behaviour when compared to constant light, the red light had a repulsive effect during the day, but not at night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…Increased potential for detection of a light source should increase with an animal's spectral sensitivity (Ford et al 2018), but we found that spectral sensitivity is not necessarily an indicator of attraction to a stimulus (sensu White et al 2005) or a light source (sensu Hansen et al 2018). One external factor that potentially affected visual perception by eastern tiger salamanders is that light transmission in a body of water is influenced by characteristics of the aquatic Table 1.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Increased potential for detection of a light source should increase with an animal's spectral sensitivity (Ford et al 2018), but we found that spectral sensitivity is not necessarily an indicator of attraction to a stimulus (sensu White et al 2005) or a light source (sensu Hansen et al 2018). One external factor that potentially affected visual perception by eastern tiger salamanders is that light transmission in a body of water is influenced by characteristics of the aquatic Table 1.…”
Section: Discussionmentioning
confidence: 87%
“…Some aquatic animals use phototaxis to move toward light in water (e.g., McConnell et al 2010, Wolf et al 2017), a behavior that potentially evolved to utilize moonlight or starlight for orientation (Thums et al 2016, Cruz et al 2018). Humans have taken advantage of this phototaxis to attract aquatic animals with artificial light during commercial fishing (e.g., teleost fish: Brown 2000, Marchesan et al 2005; cephalopods: Clarke and Pascoe 1998) or repel animals from potentially harmful human infrastructure (e.g., Hansen et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in repulsive behavior of stroboscopic light, between salmonid and cyprinids is not surprising, since Amaral et al [55] also observed a superior repulsive behavior of salmonid Chinook salmon in relation to the repulsive behavior of the cyprinid Ptychocheilus oregonensis in the Yakima River (USA). Hansen et al [56] verified that Chinook salmon, which exhibited a greater repulsive behavior to various light stimuli in the diurnal period and suggests, in its study, that this result may be related to vision and trophic factors. Nevertheless, our results also display clear behavioral differences between fish species, even inside the same family.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, differences in light intensity can change the stimulus from being repulsive to attractive (Nemeth & Andersen, 1992) and the required power for this type of lighting is a major implementation cost (Patrick et al, 1985;Brown, 2000;Richards et al, 2007). More recently, therefore, work has begun exploring a range of light frequencies and strobe frequencies of lightemitting diodes (LEDs) for improved performance (Elvidge et al, 2018;Hansen et al, 2018;Ford et al, 2017Ford et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%